Measured and simulated thermal behaviour in rammed earth houses in a hot-arid climate. Part B: Comfort. (September 2017) - Beckett, C.T.S.; Cardell-Oliver, R.; Ciancio, D.; Huebner, C.
Abstract: Heating and cooling of residential buildings consumes around ten percent of the world's energy. One approach for reducing these costs is solar passive design using building materials with high thermal mass such as Rammed Earth (RE). Several studies have examined the performance of small RE structures or individual rooms within RE dwellings and have demonstrated the material's capacity to provide comfortable internal conditions passively. However, there is a lack of scientific evidence about the performance of full RE houses in real-world settings spanning several seasons. This research investigated the thermal performance of RE structures prior to occupancy and over the course of an occupied year. Two custom-designed houses were built in the hot-arid city of Kalgoorlie-Boulder, Western Australia: one with traditional solid RE walls and the other with walls with an insulating polystyrene core (iRE). Otherwise the houses were identical in orientation and design. This study is presented in two Parts. Part A examined the houses' performance without occupants: This Part examines their occupied behaviour in terms of the occupants' thermal comfort. Comfort was examined using qualitative and quantitative data from sensor measurements as well as occupant surveys and simulated results using state-of-the-art assessment software BERS Pro . Comfort scores for measured and simulated data were determined using rules built into BERS Pro 's engine Chenath and a modified version of the ANSI/ASHRAE Standard 55-2010 SET * method. Real-world thermal comfort of both houses outperformed their simulated behaviours: occupants reported comfortable conditions throughout Summer (outdoor maxima 45 °C) and Winter (minima 1 °C) with no artificial cooling and with minimal heating. The Chenath and SET * methods agreed with comfort performance in Summer but scored Winter performance poorly. Similarly, simulations predicted poor performance in Winter. Consequently, predicted energy demands due to heating were likely far higher than those needed in reality. This paper therefore argues from measured evidence of RE and iRE houses for the suitability of RE as a sustainable building material able to curb domestic energy demands. Collected data has been made publicly available for future analyses. Abstract : Highlights: Long-range virtual sensing was used to capture internal climate data from a suite of sensors embedded in two rammed earth houses in a hot-arid climate for a full year's occupancy. Through regular surveys, occupants reported comfortable internal conditions in summer and winter with no use of artificial cooling and little need for artificial heating. Two comfort rating methods were assessed: Chenath and SET * . Both adequately judged comfort in summer. Neither method successfully judged comfort in winter because assumed heating thresholds were excessive. House energy use was likely significantly overestimated as a consequence. Data has been made publicly available for future analyses atdatascience.ecm.uwa.edu.au:55555 .